Biodeterioration and biodegradation of Roman monuments: A comparison of the current status of 18th century paintings by the Canalettos - Monge Nájera, Julián (2014)
Worldwide there is an urgent need to monitor the conditions of monuments affected by biodeterioration and biodegradation, but no long term data exist for most of them. Here is an exception in the case of certain Roman monuments whose bioderioration and biodegradation agents were painted approximately 250 years ago by Giovanni Canal and Bernardo Bellotto, the Canalettos. In our study we compare four paintings with recent photographs of the same monuments by using grid counts. The mean area affected by visible biodeterioration and biodegradation decreased less than 2% since the time of the Canalettos´s paintings (Chi-Square p < 0.004) and the improvement mostly involves higher plants. We urge others to find old paintings and photographs that can be used for similar studies in other cultural resources.